Can forest carbon projects improve rural livelihoods?: analysis of the Noel Kempff Mercado Climate Action Project, Bolivia - Asquith, N.M.; Vargas Rios, M.T.; Smith, J. (2002)
The authors studied the Noel Kempff Mercado Climate Action Project (NKMCAP), Bolivia, to assess whether forest protection carbon (C) projects can significantly benefit local people. They hypothesized that forest protection can only securely deliver C if significant stakeholders are meaningfully and transparently involved, traditional or customary rights are recognized and their loss compensated for, and there are direct linkages between conservation and development objective. The research focused on 53 members of the communities of Florida, Porvenir and Piso Firme and 36 secondary stakeholders. In each of the villages half-day meetings with community leaders was held, complemented by semi-structured one-hour interviews with 5, 10, and 7 families, representing 20%, 10% and 8% of each community. The long-term impact of the NKMCAP on the local communities may well be positive. However, in the short run, certain sections of the local communities are financially poorer. Forest protection projects clearly have the potential to sequester C, protect biodiversity and simultaneously contribute to sustainable rural development, but if they really are to improve rural livelihoods, they must be designed and implemented carefully and participatively.